Bringing back Galium aparine L. from forgotten corners of traditional wound treatment procedures: an antimicrobial, antioxidant, and in-vitro wound healing assay along with HPTLC fingerprinting study - Amirreza Dowlati Beirami; Negin Akhtari; Razieh Noroozi; Dara Hatamabadi; Syed Muhammad Farid Hasan; Seyed Abdulmajid Ayatollahi; Neda Alsadat Ayatollahi; Farzad Kobarfard (BMC, 2024)
Abstract Background The wound healing process, restoring the functionality of the damaged tissue, can be accelerated by various compounds. The recent experimental analysis highlights the beneficial effects of phytochemicals in improving skin regeneration and wound healing. In traditional medicine, one of the widespread plants used for treating different injuries or skin afflictions is Galium aparine L. (GA). Besides, previously reported chemical compounds of GA suggested its therapeutic effects for the wound healing process, yet its regulatory effects on the cellular and molecular stages of the wound healing process have not been investigated. Methods In the present study, the phytochemical profile of the GA extract was analyzed using HPTLC fingerprinting, and further scientific evaluation of its phytochemicals was done. The wound-healing effects of GA extract were explored at the cellular and molecular levels while accounting for cell toxicity. The wound closure enhancing effect, antibacterial activity, and antioxidant activity were assessed. Results The HPTLC fingerprinting of the GA extract proved its previously reported phytochemical profile including phenols, flavonoids, tannins, plant acids, ergot alkaloids, flavonoids, anthraquinones, terpenoids, sterols, salicin, lipophilic compounds, saponins, iridoids, and heterocyclic nitrogen compounds. Antimicrobial assessment, of the extract, indicated the more susceptibility of S. aureus to the inhibitory effects of GA rather than E. coli and S. epidermidis. DPPH test results revealed the antioxidant property of GA extract, which was comparable to ascorbic acid. The results of the viability assay showed no cytotoxicity effects on human umbilical endothelial cell (HUVEC) and normal human dermal fibroblast (NHDF) cell lines treated with different concentrations of whole plant extract and cell viability increased in a dose-dependent manner. The results of the scratch assay showed improved cell migration and wound closure. Conclusions This study shows the anti-oxidant, anti-microbial, and in vitro wound healing wound-healing effects of GA hydroalcoholic extract, which aligns with its use in traditional medicine. No cytotoxicity effects were shown. The results from this study can be the basis for further investigations such as animal models and phytochemical studies. Further evaluation of its effects on mechanisms and signaling pathways involved in the wound healing processes such as angiogenesis and cell proliferation can provide novel insights into the potential therapeutic effects of the GA extract.